Pentingnya atau Pengaruh Ethos Kerja dan Etika Serta Dampaknya terhadap Profesi dan Perkembangan Karir Seseorang di Dunia Kerja (International Forum of Researchers and Lecturers, 2025)
This study examines the importance of work ethos and professional ethics and their influence on career development and professionalism in the workplace. A strong work ethos, characterized by dedication, discipline, and responsibility, alongside the application of ethical principles such as integrity and honesty, positively contributes to increased productivity, reputation, and career opportunities. Using a qualitative approach through literature review and semi-structured interviews with professionals from various fields, the findings reveal that work ethos and ethics not only shape individual character but also serve as essential assets in navigating the competitive dynamics of the modern workplace. The implications of this study emphasize the need for both organizations and individuals to consistently instill these values to ensure sustainable career growth and professional excellence.